2019
DOI: 10.1111/cen3.12524
|View full text |Cite
|
Sign up to set email alerts
|

Role of diet and gut microbiota in multiple sclerosis: New findings on the role of high‐salt intake in induction of neuroinflammation

Abstract: Multiple etiological factors are involved in the pathogenesis of multiple sclerosis (MS). The recent study by Okuno et al. provides an insight into the interaction of gut microbiota and immune cells in MS. However, new findings showed that a high-salt diet is involved in the induction of severe neuroinflammation through the aggravation of T helper 17 pathways and their inflammatory cytokines. The synergistic effects of high-salt and high-fat intake in the induction of inflammatory reactions are also plausible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Research confirms the health risks of excessive salt intake, most notably the increased risk of cardiovascular disease associated with HSD [3]. Studies have also found that HSD can affect the body's immune system and may even increase the risk of autoimmune diseases [4,5]. In addition, HSD can increase the risk of gut related diseases and cancer, as well as affect the kidney system, skeletal system, and metabolic function [6,7].…”
Section: Introductionmentioning
confidence: 95%
“…Research confirms the health risks of excessive salt intake, most notably the increased risk of cardiovascular disease associated with HSD [3]. Studies have also found that HSD can affect the body's immune system and may even increase the risk of autoimmune diseases [4,5]. In addition, HSD can increase the risk of gut related diseases and cancer, as well as affect the kidney system, skeletal system, and metabolic function [6,7].…”
Section: Introductionmentioning
confidence: 95%